2017
DOI: 10.1088/1748-9326/aa83ed
|View full text |Cite
|
Sign up to set email alerts
|

Getting the numbers right: revisiting woodfuel sustainability in the developing world

Abstract: The United Nations' Sustainable Development Goals encourage a transition to 'affordable, reliable, sustainable and modern energy for all'. To be successful, the transition requires billions of people to adopt cleaner, more efficient cooking technologies that contribute to sustainability through multiple pathways: improved air quality, reduced emissions of short-lived climate pollutants, and reduced deforestation or forest degradation. However, the latter depends entirely on the extent to which people rely on '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 30 publications
(48 reference statements)
1
31
0
Order By: Relevance
“…Our simulations show that under a reasonable set of assumptions about woody biomass growth and harvest, Haiti will likely experience levels of fNRB that are much lower than other assessments report [50]. These results support recent analyses that argue for a 8 .…”
Section: Discussionsupporting
confidence: 80%
“…Our simulations show that under a reasonable set of assumptions about woody biomass growth and harvest, Haiti will likely experience levels of fNRB that are much lower than other assessments report [50]. These results support recent analyses that argue for a 8 .…”
Section: Discussionsupporting
confidence: 80%
“…Estimates from the literature reveal extenstive uncertainties when it comes to the fraction of nonrenewable biomass (fNRB) in Cameroon. This uncertainty is also the case in many other countries and regions (Bailis et al 2017). In a spatially explicit assessment of pantropical fuelwood supply and demand, Bailis et al (2015) found that the fNRB related to wood that was directly harvested as fuel was lower than 10% in Cameroon.…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%
“…This estimate did not account for the fuelwood that was a by-product of various land cover changing processes not primarily related to fuel production. In a recent study on carbon-offsets projects, Bailis et al (2017) estimated the fNRB in a range of projects in African regions, including one gold-standard project in Cameroon. For that project, the authors were not able to assess the fNRB, which was estimated at 0%-100%.…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%
“…The financing risks relate to covering the cost of forest management interventions and supporting the purchase of improved technology for charcoal production (kilns) and charcoal consumption (cookstoves). Charcoal production is widely considered to be a significant cause of deforestation and forest degradation, although the precise causal pathway is distorted by links to other drivers of forest degradation such as timber extraction, grazing of livestock, and clearing of forests to make way for crop production (Bailis et al, 2017;Hosonuma et al, 2012). According to many stakeholders, there is almost no financing available to fund the farm forestry and reforestation interventions necessary to establish a sustainable supply of biomass for charcoal production and to maintain forest cover.…”
Section: Historical Perspective On Charcoalmentioning
confidence: 99%